Answer :

isacrispa3

Answer:

f(n) = 37 (0.3)ⁿ⁻¹

Step-by-step explanation:

i belive that is what it is

Explicitly writing the formula one finds that it corresponds to  [tex]f(n) = f(1)+2^{(n-1)}[/tex]

Given the following information about this formula we have:

  • f(1) = 0
  • f(n) = f(n-1)+2

How to calculate the formula explicitly?

The information from the utterance must be used and thus always decrease one from the original function. In that case:

[tex]f(1) = f(1)+2^0 = 0\\f(2) = f(1)+2^1 = 2\\f(3) = f(2)+2^2 = 4\\f(4) = f(3)+2^3 = 8\\f(n) = f(1)+2^{(n-1)}[/tex]

See more about formula at brainly.com/question/20748250

#SPJ2

Other Questions